The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1002/polb.24908
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Dynamic Viscoelasticity of Single Polymer Chains using Atomic Force Microscopy

Abstract: In single‐molecule force spectroscopy (SMFS), many studies have focused on the elasticity and conformation of polymer chains, but little attention has been devoted to the dynamic properties of single polymer chains. In this study, we measured the energy dissipation and elastic properties of single polystyrene (PS) chains in toluene, methanol, and N,N‐dimethylformamide using a homemade piezo‐control and data acquisition system externally coupled to a commercial atomic force microscope (AFM), which provided more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 53 publications
1
16
0
Order By: Relevance
“…In the past, the viscoelasticity of single polymer chains has been determined by oscillatory response [ 42 , 43 , 44 ]. As opposed to the present work, these studies used oscillation frequencies close to the resonance of the cantilever and measured dissipation for a polymer from changes in phase lag.…”
Section: Resultsmentioning
confidence: 99%
“…In the past, the viscoelasticity of single polymer chains has been determined by oscillatory response [ 42 , 43 , 44 ]. As opposed to the present work, these studies used oscillation frequencies close to the resonance of the cantilever and measured dissipation for a polymer from changes in phase lag.…”
Section: Resultsmentioning
confidence: 99%
“…In the context of extracting viscoelastic information, oscillatory measurements have been performed on single molecules [50][51][52]. In contrast to the present study, these measurements were performed with oscillation frequencies close to cantilever resonance and have reported dissipation for single molecule.…”
Section: Force-extension Measurementmentioning
confidence: 87%
“…In this study, to measure the dynamic viscoelasticity of single polymer chains, we equipped an external oscillation control and data acquisition system based on traditional AFM (Figure S1). 34 A lock-in amplifier was introduced into the system to provide flexible experimental control and data acquisition. While the polymer chain was stretched, the AFM cantilever was oscillated at the resonant frequency by an external excitation signal from the lock-in amplifier, as shown in Figure 1b.…”
Section: Materials and Sample Preparationmentioning
confidence: 99%
“…We found that the viscosity of a PS chain was mainly determined by its interaction with the solvent. 34 In this study, we used this dynamic SMFS method to quantitatively measure the dynamic viscoelastic changes in elasticity and viscosity of a single chain at low elongation. By quantitatively analyzing the changes in elasticity and viscosity of a single chain at the low elongation, the interaction of PNIPAM molecules with water was investigated to reveal the hydration mechanism of the single polymer chain.…”
Section: Introductionmentioning
confidence: 99%